Social Problems in Brasov City. The Perspective of Social Workers from the Private Sector - Mihaela Gotea (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
The paper presents the results of research conducted with social workers from the private sector in Brasov city. Data was collected using the focus-group method. The participants were social workers who work with different vulnerable groups and in different non-governmental organizations. Data obtained were analyzed using thematic coding, which resulted in four main categories, each with a variety of sub-categories For example, the fourth category, the social workers' visions regarding the most efficient solutions of current social problems, has different subcategories, which were: changes of national strategy, changes in the human resource in the system, and development of new social services. Solving social problems can be done either from the outside (inducing a point of view that is identified with the official policy of state institutions) or from the inside (identifiable with the vision of the minority groups involved in these social problems).